2022
DOI: 10.1371/journal.pntd.0010286
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic landscape of hepatic lymph nodes, peripheral blood lymphocytes and spleen of swamp buffaloes infected with the tropical liver fluke Fasciola gigantica

Abstract: The tropical liver fluke Fasciola gigantica is a parasitic helminth that has been frequently reported to infect mammals, typically involving water buffaloes. In this study, we characterized the tissue transcriptional landscape of buffaloes following infection by F. gigantica. RNAs were isolated from hepatic lymph nodes (hLNs), peripheral blood lymphocytes (pBLs), and spleen at 3-, 42- and 70-days post-infection (dpi), and all samples were subjected to RNA sequencing analyses. At 3 dpi, 2603, 460, and 162 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Overall, the enriched pathways and processes indicate that an immune response was happening in the sheep treated with commercial vaccines. In livestock, few studies have been made on the spleen transcriptome after an infection and the enriched terms in these works were similar to those detected in the present study ( 39 42 ).…”
Section: Discussionsupporting
confidence: 87%
“…Overall, the enriched pathways and processes indicate that an immune response was happening in the sheep treated with commercial vaccines. In livestock, few studies have been made on the spleen transcriptome after an infection and the enriched terms in these works were similar to those detected in the present study ( 39 42 ).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, ref. [ 55 ] reported that the ADH5 gene may be related to selection for growth in Nellore cattle. All these ADH genes were detected in our work, but enriched for different pathways, such as FA metabolism, pyruvate metabolism, and glycolysis.…”
Section: Discussionmentioning
confidence: 99%